Regional heterogeneity in muscle fiber strain: the role of fiber architecture - Azizi, E.; Deslauriers, Amber R. (Frontiers in Physiology, 2014)
The force, mechanical work and power produced by muscle fibers are profoundly affected by the length changes they undergo during a contraction. These length changes are in turn affected by the spatial orientation of muscle fibers within a muscle (fiber architecture). Therefore any heterogeneity in fiber architecture within a single muscle has the potential to cause spatial variation in fiber strain. Here we examine how the architectural variation within a pennate muscle and within a fusiform muscle can result in regional fiber strain heterogeneity. We combine simple geometric models with empirical measures of fiber strain to better understand the effect of architecture on fiber strain heterogeneity. We show that variation in pennation angle throughout a muscle can result in differences in fiber strain with higher strains being observed at lower angles of pennation. We also show that in fusiform muscles, the outer/superficial fibers of the muscle experience lower strains than central fibers. These results show that regional variation in mechanical output of muscle fibers can arise solely from architectural features of the muscle without the presence of any spatial variation in motor recruitment.